Meningkatkan Hasil Belajar IPA Materi Perubahan Wujud Benda Menggunakan Video Animasi Pada Siswa Kelas IV SDK 077 Kewapante - Orpa Ale Hade; Maria Helvina; Marianus Yufrinalis (Departement of Mathematics Education, 2023)
This study aims to improve science learning outcomes material changes in the form of objects. This research is Classroom Action Research (PTK) conducted in 2 cycles where each cycle consists of 3 meetings, which consists of 4 stages, namely planning, implementing, observing and reflecting. The subjects in this study were fourth grade students at SDK 077 Kewapante, totaling 37 students consisting of 23 male students and 14 female students. Data collection techniques used in this study were tests, observation and documentation. The data analysis technique used is the analysis of test results and observation results. The research results show that the use of animated videos can improve student learning outcomes. The increase in student learning outcomes can be seen in the results of the pretest cycle I with a total score of 1,479 with an average of 39.9, and the percentage of completeness of 5.4% increased 45.9% to the results of the posttest cycle I where the total value was 3,028 with an average of 81. 8 and the percentage of completeness is 51.3%. while in cycle II there was an increase with a total value of 3,450 with an average of 93.2 and a completeness percentage of 100%.